Structure-antifungal activity relationship of cinnamic acid derivatives - Bisogno, Fabricio Román (2007)
A structure-antifungal activity relationship (SAR) study of 22 related cinnamic acid derivatives was carried out. Attention was focused on the antifungal activities exhibited against Aspergillus flavus, Aspergillus terreus, and Aspergillus niger. (E)-3-(4-Methoxy-3-(3-methylbut-2-enyl)phenyl)acrylic acid (16) exhibited antifungal activity against A. niger, comparable to that of miconazole and a significant antifungal effect against A. flavus and A. terreus as well. A structure-activity relationship (SAR) study of related cinnamic acid derivatives has allowed a model to be proposed for the recognition of the minimal structural requirements for the antifungal effect in this series.